Penghilangan Mikroorganisme dalam Air Minum dengan Dielectric Barrier Discharge - Ariadi Hazmi; Reni Desmiarti; Eka Putra Waldi; Arief Hadiwibowo; . Darwison (Jurnal Rekayasa Elektrika, 2012)
Microorganisms such as Escherichia coli in water are a component that is difficult to remove in conventional water treatment systems. Several systems have been implemented to reduce levels of microorganisms is the use of disinfectants, the membrane filtration and activated carbon absorption. These systems have several weaknesses, so that not all microorganisms can be removed from drinking water. The plasma system is an applicable technology for removing organic compounds and microorganisms in drinking water. By creating plasma in water will produce several of active species such as OH-, H+, O3 and H2O2 that has a high oxidation potential, decompose organic compounds and kill microorganisms in the water significantly. This paper will describe the removal of microorganisms in drinking water using a plasma system by the method of dielectric barrier discharge (DBD ). The results howed that the pH of drinking water produced in the range 6.5 to 7.3. The higher voltage causes the higher the conductivity, temperature and ORP water. Removal efficiency for the content of microorganisms Coli Fecal and Coliform in the range 99.2 to 100% after water was injected voltage of 13-17 kV for 10 minutes.